'Locked rehabilitation': a need for clarification. (February 2016) - Dye, Stephen; Smyth, Lucy; Pereira, Stephen
Summary: Recently, the term 'locked rehabilitation' has spread from commissioning to now also clinical parlance. This is without any clear service description or category of patient which this service manages. Differences between this new term and an established definition of low secure services are examined and reasons for the introduction of this terminology are discussed. This is contextualised within service development, payment by results and measures of quality. It is argued that there is a need for ongoing measurements of types of patients admitted to, and treatments offered by, this 'new' ward, as well as those within psychiatric intensive and low secure care services.